ANALISIS MANAJEMEN BISNIS SYARIAH PENGARUH INFORMASI DAN PEMBERIAN HADIAH TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE (STUDI PADA PENGGUNA BUKALAPAK DI KECAMATAN PAMIJAHAN DAN CIBUNGBULANG, KABUPATEN BOGOR, JAWA BARAT) - Andini, Sulian Nur; Suryani, Ermi; Melinasari, Susi (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2024)
This study aims to determine the variables that influence consumer purchasing decisions which consist of information and gift giving on the Bukalapak platform. This type of research is quantitative research with a survey approach. The population in this study were Bukalapak users in Pamijahan and Cibungbulang Districts. The sample used is using accidental sampling technique, amounting to 100 respondents. With the data collection method used is the distribution of questionnaires. data analysis using multiple regression analysis.The results of multiple regression analysis show that the information variable (X1) partially influences online purchasing decisions (Y) for Bukalapak application users in Pamijahan and Cibungbulang Districts in an Islamic Perspective. with a t-count value of 3.554 > t-table of 1.98472 and a significant value of 0.001 <0.05. And the gift giving variable (X2) partially influences online purchasing decisions (Y) with a t-count of 8.604 > t-table of 1.98472 with a significance value of 0.000 <0.05. And the variables of information and gift giving simultaneously have a significant effect on online purchases (Y) for Bukalapak application users in Pamijahan and Cibungbulang Districts in a Sharia Business Management Perspective. with a calculated F value of 103.7895 > F table of 3.09. Thus the entire hypothesis proposed is proven and acceptable. It can be concluded based on the results of partial and simultaneous and gift giving influence online purchasing decisions from a Sharia Business Management perspective on Bukalapak users in Pamijahan and Cibungbulang Districts.